INOVASI KURIKULUM INKLUSIF SEBAGAI UPAYA MENGOPTIMALKAN POTENSI SISWA - Arbianti, Selsha (AHSANTA JURNAL PENDIDIKAN, 2024)
The right of every citizen to receive quality education is enshrined in the Republic of Indonesia Law No. 20 of 2003 on the National Education System. Citizens with physical, emotional, mental, intellectual, and/or social disabilities also have the right to receive special education. Inclusive education is an approach that provides opportunities for children with special needs (ABK) to learn alongside their peers in regular schools. To meet diverse learning needs, innovative inclusive curricula become essential. With flexible and varied curricula, we can ensure that every student, including those with special needs, has the opportunity to develop their potential to the fullest. This research uses a literature study design to explore more deeply the innovation of inclusive curricula as an effort to optimize student potential. The development of inclusive curricula needs to be carried out to improve the quality of inclusive education. The community can contribute by raising awareness about the importance of inclusive education and eliminating stigma against children with special needs.